Seletividade de feijão a herbicidas (Phaseolus vulgaris) - Aranha, Jean Lukas Mendes (2017)
Common bean (Phaseolus vulgaris) is a short cycle crop. Due to this characteristic, a weed interaction is a factor that must be approached in a caring way, because the damage caused by competition as weeds is high. The control of weeds in large areas of the crop, would be impracticable with weeds, being used the chemical control that obtains greater practicality, high efficiency, quickness. It is necessary to point out that the plants of interest may have different susceptibilities to the herbicides used for the beans, causing damage to plants such as: phytotoxicity, reduction of plant height, dry matter, green matter and foliar area. The objective of this study was to evaluate the selectivity of herbicides different from bean cultivars, among them from the pinto beans group (Celeiro and Curió) and from the black group (Uirapuru and Tuiuiu). The experiment was conducted outdoors in the city of California-PR. They were seeded in cups of 500mL to 4 cm of depth filled with local soil, three seeds of each cultivar, and later thinning, leaving only one seed. The experiment was carried out in a completely randomized design (DIC) in factorial (4x3) with 4 replicates. The herbicides used were: Fomesafem 1L / ha-1, Imazaquim 1L / ha-1, and Quizalofop-p-tefurilico 0.6L / ha-1. After application, phytotoxicity of 0-28 days was analyzed at intervals of 7 days, plant height with a ruler graduated in millimeters, dry matter, green matter, leaf area in cm². The cultivar TUIUIU and CURIO in pre-emergence, with the use of the herbicide fomesafem and Quizalofope-P-tefurílico respectively, observed necrotic lesions,reducing leaf area, stature, dry matter and green matter. In the UIRAPURU cultivar the use of herbicides such as imazaquir caused 60% phytotoxicity when applied in emergence, similar symptoms occurred in the CELEIRO cultivar, but in a pre emergence.